SCHOOL HEALTH PROMOTION: A QUASI-EXPERIMENTAL STUDY ON CLEAN AND HEALTHY LIVING BEHAVIOR AMONG ELEMENTARY STUDENTS IN JAYAPURA, PAPUA, INDONESIA - Ellen Rosawita Veronica Purba; Lely Lusmilasari; Janatin Hastuti (Belitung Raya Foundation, 2020)
Background: The Indonesian government has launched a clean and healthy living behavior program as one of the efforts for school health promotion. However, the healthy behaviors of the elementary students remain low. Objectives: This study aimed to examine the effect of audiovisual-based education on the knowledge and attitudes of clean and healthy behavior in elementary students. Methods: This was a quasi-experimental study with a pretest-posttest comparison group design conducted from 1 October to 17 October 2018. A total sample of 272 students was selected using purposive sampling, with 136 assigned in an experimental group (audiovisual group) and a comparison group (poster only group). Knowledge and attitudes of clean and healthy living behavior were measured using validated questionnaires. Data were analyzed using a paired t-test and independent t-test. Results: There was a significant effect of the interventions given in the experimental and comparison group on knowledge and attitude of clean and healthy living behavior (p<0.05). However, the experimental group showed a higher mean score compared to the comparison group in knowledge and attitudes, which indicated that the use of audiovisual-based education was more effective than the use of poster alone in improving the knowledge and attitudes of clean and healthy living behavior. Conclusion: The students who received audiovisual-based education had higher knowledge and attitudes of clean and healthy living behavior than those who only received poster-based education. This study provides input for pediatric and community nurses to provide better health education for the community, specifically for school health promotion.